The Role of Universitas Terbuka-Indonesia in Improving Higher Education Services in Indonesia - Jayanti Armida Sari; Darmanto Darmanto; Heri Wahyudi; Isnaeni Yulianti (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2023)
This study examines UT Indonesia's experience and learning in an effort to expand the quantity and improve the quality of higher education in Indonesia. The aim is to comprehensively analyze the role of UT Indonesia in providing higher education services, increasing the outreach of higher education, and quality assurance. This study uses literature studies to assess, critique, and synthesize literature on research topics that allow for the emergence of new theoretical frameworks and perspectives. The review process includes four phases: design, implementation, analysis, and finally writing a review. Studies show that UT Indonesia has a very important role in optimizing the field of higher education for the community. UT's excellence as a distance university is largely determined by the quality of service in the form of student satisfaction. In addition, with the characteristics of the distance education system, UT can be considered as a solution to various educational problems, especially those related to equity and democratization of education, as well as expanding access to quality education for all levels of society across time and space. Lastly, high-tech learning models and quality assurance systems can be implemented based on ICT. It is important to use a quality circle approach in developing DE courses and learning materials for students. UT has an important role in improving the accessibility and quality of ICT-based education in Indonesia because of its cost effectiveness and flexibility in the implementation of learning.